1974
DOI: 10.4319/lo.1974.19.2.0223
|View full text |Cite
|
Sign up to set email alerts
|

Bicarbonate and carbonate ion‐pairs and a model of seawater at 25°C1

Abstract: The apparent (stoichiometric) association constants for the formation of ion-pairs between bicarbonate and carbonate and the major cations of seawater at 25°C were dctcrmined experimentally.The results wcrc used, in conjunction with earlier data on sulfate ion-pairs, to calculate the concentrations of the major species present in scawatcr.Here we measured the apparent (stoichiometric) association constants for the formation of bicarbonate and carbonate ion-pairs with sodium, calcium, and magnesium ions at 25°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
29
0

Year Published

1975
1975
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(36 citation statements)
references
References 15 publications
5
29
0
Order By: Relevance
“…Data of Neuman et al, 64 Hostetler, 65 Langmuir, 66 Nakayama, 67 Jacobson and Langmuir, 63 Martynova et al, 68 Pytkowicz and Hawley, 69 Siebert and Hostetler, 70 Plummer and Busenberg, 27 Le Guyader et al, 71 Busenberg et al, 72 and Busenberg and Plummer 73 are listed. The tabulated values are not very consistent, as was also observed by Burton.…”
Section: -18 De Visscher Et Almentioning
confidence: 99%
See 3 more Smart Citations
“…Data of Neuman et al, 64 Hostetler, 65 Langmuir, 66 Nakayama, 67 Jacobson and Langmuir, 63 Martynova et al, 68 Pytkowicz and Hawley, 69 Siebert and Hostetler, 70 Plummer and Busenberg, 27 Le Guyader et al, 71 Busenberg et al, 72 and Busenberg and Plummer 73 are listed. The tabulated values are not very consistent, as was also observed by Burton.…”
Section: -18 De Visscher Et Almentioning
confidence: 99%
“…Based on this idea, and the data of Table 8, an equation of the form A þ B=T was fitted to the data, transformed to Eq. (94) 69 were discarded as they reported stoichiometric instead of thermodynamic constants and the results deviated by almost an order of magnitude from other data; for lg K CaHCO þ 3 , the datum of Neuman et al 64 was discarded because the temperature of the experiment was not reported, 013105-19 IUPAC-NIST SOLUBILITY DATA SERIES. 95-1 and because of deviation from the other data.…”
Section: -18 De Visscher Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…It must be remembered that artificial sea water without boric acid demonstrated no low frequency relaxation frequency. As indicated in Table 6, the relaxation frequencies indicate no major variation until NaHCO, Garrels and Thompson (1962) and reviewed by Pytkowicz and Hawley (1974) and Whitfield (1974 As previously noted, Dyrssen and Hansson (1973) and Byrne and Kester (1974) Table 9. Using these data, the rate constants and equilibrium 117 Ill constants for the second step of equation were calculated using procedures previously described.…”
mentioning
confidence: 70%